REPRESENTATION OF SOCIAL ACTORS IN REPUBLIKA.CO.ID AFTER INAUGURATION OF MOCHAMAD IRIAWAN AS ACTING OF WEST JAVA GOVERNOR, INDONESIA - Bernadus Wahyudi Joko Santoso; Mohamad Yusuf Ahmad Hasyim; Maria Johana Ari Widayanti; Eko Widianto (Masyarakat Linguistik Indonesia, 2022)
The purpose of this study is to investigate social actors' representation on the inauguration of Acting Governor in West Java 2018, from Ahmad Heryawan (Aher), representing the Right Islamic Party, to Commissioner General Mochamad Iriawan (Iwan), representing the Nationalist Party, in the perspective of Critical Discourse Analysis (CDA) Theo van Leeuwen model (2008). Method of data collection were the method of reading, namely the intensive and comprehensive reading. We read the social actor’s representations that were represented in mass media online: Republika.co.id during 3 days of news, on 18, 19, and 20 of June 2018 where there was a lot of polemics over the Irawan’s inauguration. The Republika.co.id was more inclined than supported the inauguration, though according to Indonesian Government, it was legal because in that moment Irawan was as Main Secretary of the National Resilience Institute (Lemhannas), not as an active Chief of Police in Special Capital Region, Jakarta. The data were obtained by copying-paste technique. The analytical methods used were descriptions, interpretations, and explanations. The results of the analysis showed that all pro-government social actors, both in government and